(untitled) (Semiárida, 2023)
Panicum dichotomiflorum subsp. dichotomiflorum is recorded for the first time in the Río Negro province. Morphological and ecological data are provided, and aspects related to the importance of the taxon in the different production systems of the province are discussed. As an invasive taxon in the rest of the world and due to its capacity to behave as a weed, its presence must be considered important.